Empowering Adolescents in the Digital Era: A Comprehensive Approach to Digital Well-being - Febrieta, Ditta; Gina, Fathana (Nusantara Journal of Behavioral and Social Science, 2024)
The rapid proliferation of digital technologies has profoundly impacted adolescents, presenting both opportunities and challenges to their well-being. This study explores the concept of digital well-being among adolescents, focusing on the multidimensional nature of digital satisfaction, safe and responsible behavior, and overall digital health. Through a comprehensive review of existing literature, this research identifies key factors influencing digital well-being, such as gender differences, socioeconomic status (SES), and cultural background. The findings suggest that effective interventions must be tailored to account for these contextual factors. Cognitive-behavioral therapy (CBT) and family-based interventions are highlighted as promising strategies, though their success may vary depending on cultural perceptions of digital technology and mental health. Additionally, the study underscores the importance of digital literacy as a protective factor, particularly for girls and low-SES adolescents who are more vulnerable to negative digital experiences. This research contributes to the growing body of knowledge on digital well-being by integrating these diverse factors into a cohesive framework. The practical implications for psychologists, educators, and policymakers are significant, offering actionable insights for developing targeted interventions to support adolescents in navigating the digital age. Further research is recommended to explore the nuanced effects of active versus passive technology use and to assess the effectiveness of various interventions across different cultural contexts.